THE INFLUENCE OF LEARNING MODELS (PJBL & PBL) AND LEARNING STYLES (VISUAL & AUDITORY) ON BIOLOGY LEARNING OUTCOMES - Ratnaya, I Gede; Son, Rosalina Sisilia Santriana Son; Billik, Agsen H.S.; Bago, Adam Smith (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This study aims to determine: (1) Differences in biology learning outcomes between students taught with PJBL (project based learning) learning model and biology learning outcomes of students taught with PBL (problem based learning) learning model (2) Differences in biology learning outcomes between students who have a visual learning style and who have an auditorial learning style, (3) interaction between learning models and learning styles on biology learning outcomes. The research method used a quasi-experimental method with a research design =faktorial 2 x 2. The data analysis technique used two-way ANOVA at a significant level of 0.05. The results showed that: From the results of the hypothesis obtained sig value in hypothesis 1, namely the learning model 0.005 <0.004 means it can be concluded that there is a difference in the ability of learning outcomes given the PJBL AND PBL learning model, from the sig value in hypothesis 2 learning style 0.671>0.005 it can be concluded that there is no difference in the ability of learning outcomes of students with audio and visual learning styles and from the significant value in hypothesis 3 interaction between learning models and learning styles with a value of 0.766>0.005 there is no effect of interaction